Characteristics of body composition and cardiometabolic risk of Japanese male heavyweight Judo athletes. Issue 1 (December 2015) - Murata, Hiroko; Oshima, Satomi; Torii, Suguru; Taguchi, Motoko; Higuchi, Mitsuru
Abstract Background The purpose of this study was to clarify the characteristics of body composition and cardiometabolic risk of Japanese male heavyweight Judo athletes compared with heavyweight athletes of other sports. Methods Nineteen heavyweight Judo athletes (mean age, 20.4 ± 1.1 years), as well as 22 heavyweight (mean age, 21.5 ± 0.9 years) and 17 nonheavyweight (mean age, 21.1 ± 0.8 years) American football and Rugby football athletes in Japan participated in this study. Body composition was assessed by using dual-energy X-ray absorptiometry and magnetic resonance imaging. Cardiometabolic risk was evaluated by measuring blood biochemical variables. Results Heavyweight Judo athletes had significantly heavier body mass (122.7 ± 13.1 kg vs. 99.0 ± 8.1 kg), higher body fat percentage (27.5 % ± 5.2 % vs. 19.4 % ± 4.7 %), and larger visceral fat cross-sectional area (118 ± 35 cm2 vs. 67 ± 24 cm2 ) (P  < 0.01) compared with heavyweight football players. Although the cardiometabolic risk was higher in heavyweight athletes compared to nonheavyweight athletes, there were no significant differences between heavyweight Judo and heavyweight Football athletes in the blood biochemical variables, except for high concentration of uric acid in heavyweight Judo athletes. Conclusions Even though heavyweight Judo athletes had more excess fat mass, especially VF mass, their cardiometabolic risk in terms of blood biochemical parameters was not significantly higher compared with heavyweight athletes of other sports. Therefore, excessive fat accumulation may not necessarily increase cardiometabolic risk for heavyweight Judo athletes. Trial registration This trial is registered with the University Hospital Medical Information Network Clinical Trial Registration (UMIN-CTR)UMIN000020564 .